Different every night : freeing the actor - Alfreds, Mike (Nick Hern Books, 2014)
"A top-ranking director sets out his rehearsal techniques in this invaluable handbook for actors and directors. Different Every Night is the culmination of a lifetime of work in the theatre, the most complete rehearsal methodology in print since Stanislavsky. It offers a vital masterclass for actors and directors, full of sound practical advice and guidance, and is packed with techniques for bringing the text to life and keeping it alive - both in rehearsal and performance. ''Most of what I am as an actress I owe to Mike Alfreds. He gave me the language and the tools I needed for my craft."--Publisher's description.